TITLE : Chemical management of foliage feeding barley aphids (Rhopalosiphum maidis) - Patel, Ashok - (Journal of Cereal Research, 2015)
ABSTRACTThe present investigation was undertaken to find most effective insecticide to include IPM practice of foliar aphid of barley for which seven insecticides as sprays viz., Imidacloprid 200 SL, Thiamethoxam 25WG, Flubendiamide 480 SC, Quinalphos 25 EC, Dimethoate 30 EC, Acetamiprid 20 SP and Clothianidin 50 WDG were evaluated. All these insecticides were found significantly superior over control. However Flubendiamide 480 SC @250ml/ha. was Â most effective against barley aphid and being safer to natural enemies, it might be best fit in integrated pest management module of barley aphid followed by Clothianidin 50 WDG @30 gm/ha and Thiamethoxam 25WG @50gm /ha.. Flubendiamide 480 SC @ 250ml/ha. recorded highest yield of 48.29 q/ha which was at par with Clothianidin 50 WDG @ 30 gm/ha (47.71q/ha.), Acetamiprid 20 SP @ 100gm/ha. (47.63 q/ha) and significantly better over untreated control (38.21 q/ha).Â